Use of antifungals in pediatric superficial dermatophytosis - Grishma R Gandhi; Resham J Vasani (Wolters Kluwer Medknow Publications, 2020)
There has been a rise in the incidence of dermatophytic infections in children in the last decade. Additionally, there has been a sea change in the clinical presentation, treatment practices and course of the condition seen in practice. This article summarises information on the available topical and oral antifungal agents in question and asnwer format for better understanding.